Reading performance of Malaysian students across gender in PISA 2012 - Marlia Puteh,; Zuhana Mohd Zin,; Ihsan Ismail, (Penerbit Universiti Kebangsaan Malaysia, 2016)
The 2012 PISA reading literacy aims to measure 15 year-olds’ reading performance in preparing them to meet real-life challenges. The primary aim of the present study is to examine Malaysian students’ reading performance by comparing the girls’ and boys’ performances in PISA 2012. The 2012 PISA reading literacy framework comprises three important reading aspects: access and retrieve (AR), interpret and integrate (II), and reflect and evaluate (RE). These aspects were further examined through the students’ reading performance in five types of text namely narration, exposition, argumentation, description and instruction. The findings demonstrate that the students performed better in AR than in II and RE indicating a better performance in lower-order reading skills than in the higher-level reading aspects. Findings also show that girls outperformed the boys across all reading aspects and types of reading texts. This paper concludes by emphasizing the need to integrate higher-order reading skills in the reading curriculum in order to prepare Malaysian students for better literacy competency.